Aquaculture in Malaysia - challenges and opportunities - Ang, Kok Jee (1988)
Aquaculture is a recent development in Malaysia. Under the National Agriculture Policy, the Malaysian Government is committed to develop aquaculture into a major industry by the year 2000. This papaer reviews the development of aquaculture in Malaysia. It discusses the projected and actual production achieved so far and the potential for future development. Some of the major problems facing the industry are highlighted. These are in relation to site selection, water quality and management. In 1986 there were 475.8 ha of brackishwater ponds, 82,259m2 of brackishwater cage culture, 4,446 ha of cockle farms 2594 ha of freshwater ponds, 8,101 m2 of freshwater cage culture and 1,296 ha of disused mining pools. The total production for 1986 was 51,643,7 tonnes and cokle constituted about 88.4% of the production,while 9.2% was represented by freshwater fish production. This constituted to about 10% of the fish landings in Malaysia. Malaysia has vast areas for aquaculture development. She has 570,000 ha of mangrove forests,extensive mudflats,17,200 ha of disused mining pools and over 200,000 ha of impounded waters. It has been projected that by the year 1990 a total production of 135,932 tonnes would be achieved and by the year 2000 a total production of 206,070 tonnes is projected. Wether the projected production could be met would depend on several factors. These are explained in the paper.